Enterprise budget survey: An analysis of crop and livestock enterprises - Malaiyandi, Sangeetha; Bayite-Kasule, Stephen; Mugarura, Samuel (International Food Policy Research Institute, 2010)
Uganda has experienced strong economic growth in recent years with GDP growth among the highest in Africa at an average annual rate of 7.2 percent from 2000-2008 (WDI, 2009). The most recent study by the World Bank shows that strong poverty reduction efforts have also halved poverty levels throughout the country since the early 1990's, a commendable achievement considering the declines in world prices of key national exports. Despite this achievement, poverty remains a persistent problem, especially among agriculture households who account for almost half of all poor households in the country (World Bank, 2005). The agriculture sector continues to play an important economic role in Uganda, accounting for almost 23 percent of GDP (2008). Almost 70 percent of the country's labor force is employed in agriculture (World Bank, 2005). In an effort to continue its public commitment to poverty reduction, the Ministry of Agriculture, Animal Industries, and Fisheries has established national strategy plans for the improvement of the agricultural sector. From 2000 until early 2010, the guiding strategy was the Plan for the Modernisation of Agriculture (PMA), the implementation of which was led by the PMA Secretariat. In fulfilling its mission, the PMA Secretariat identified key agricultural enterprises throughout the country and undertook research to determine avenues and opportunities for improving agricultural productivity through supporting smallholder farmers. Within the context of the Uganda Agricultural Strategy Support Program that links the two institutions, the PMA Secretariat requested IFPRI-Kampala to assist it in its efforts to better understand the profitability and productivity of these key crop and livestock enterprises in Uganda.